1998
DOI: 10.1039/a804623i
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a covalently attached multilayer via photolysis of layer-by-layer self-assembled films containing diazo-resins

Abstract: Construction of highly stable covalently attached multilayer films was achieved by UV irradiation of ionic self-assembled multilayer films of diazo-resins and poly(sodium styrene sulfonate).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 163 publications
(118 citation statements)
references
References 4 publications
3
115
0
Order By: Relevance
“…8) and comprises conducting and light-emitting polymers 89,112, , other non-conjugated redox-active polymers 49,62,131,132,[200][201][202][203][204][205][206][207] , polymeric complexes such as the Cu 2+ complex of poly(ethyleneimine) 80) , Ru 2+ complex of 2,29-bipyridyl containing polymers 170-172, 200, 208) , or an Os 2+ complex of poly(vinylpyridine) 196,[209][210][211] , reactive polymers 35,87,148,[212][213][214][215][216] , polymers bearing non-linear optically active dyes 35,138,148,214,[217][218][219][220][221][222][223][224][225][226] , liquid crystalline polyelectrolytes 105,[135][136][137] , and dendrimers [227]…”
Section: Polymers Suited For Esamentioning
confidence: 99%
“…8) and comprises conducting and light-emitting polymers 89,112, , other non-conjugated redox-active polymers 49,62,131,132,[200][201][202][203][204][205][206][207] , polymeric complexes such as the Cu 2+ complex of poly(ethyleneimine) 80) , Ru 2+ complex of 2,29-bipyridyl containing polymers 170-172, 200, 208) , or an Os 2+ complex of poly(vinylpyridine) 196,[209][210][211] , reactive polymers 35,87,148,[212][213][214][215][216] , polymers bearing non-linear optically active dyes 35,138,148,214,[217][218][219][220][221][222][223][224][225][226] , liquid crystalline polyelectrolytes 105,[135][136][137] , and dendrimers [227]…”
Section: Polymers Suited For Esamentioning
confidence: 99%
“…A first method consists in cross-linking the films after their buildup, as first introduced in 1995 by Decher et al [41] In 1998, the group Sun et al constructed a highly stable covalently attached multilayer obtained by UV irradiation of ionic self-assembled multilayer films of diazo-resins and poly(styrene sulfonate). [42] In 1999, Harris et al [43] showed that cross-linking of polyelectrolyte films containing amine and carboxylic groups can be achieved by simple heating resulting in the formation of amide functions. In 1996, Brynda and Houska used a cross-linking agent, glutaraldehyde, to cross-link human serum albumin/heparine multilayers.…”
Section: Reviewmentioning
confidence: 98%
“…The noncovalently attached films are not robust enough and can be etched by solvents, which limits application of this type of film in an extended range. A way we designed to solve this problem is to combine the simplicity of the layer-by-layer assembly technique with post photoinduced reaction in the restricted area [21]. We first selected the diazonium group containing polycation of diazoresins (note DAR) (Scheme 1E) and sulfonate containing polyanion of poly(4-styrene sulfonate) (PSS) as building blocks.…”
Section: In Situ Photoreaction To Fabricate Covalently Attached Multimentioning
confidence: 99%